ONOMASTIC EATERY PLACES IN AMBON CITY - Intan Ayu Sabrina; Dianita (English Education Department of STKIP Pasundan, 2024)
This study reviews the linguistic analysis of naming eating places in Ambon. This research focuses on the use of language in naming places to eat, especially in terms of monolingual, bilingual, or multilingual, as well as the categories used in naming, such as mythology, adjectives, time, family, tools, places, and names of people. Data was obtained through Website observation and Google Maps from January to March 2024. The results show the dominant use of Indonesian and English in monolingual form and the tendency to use Indonesian with local or foreign languages in bilingual form. Some names also contain mythological elements, tools, or adjectives that add an artistic dimension to the culinary experience. This study provides a better understanding of language use in naming food establishments in Ambon and contributes to the understanding of local culture and identity.